A subjetivação altermnemônica como constituição da memória: uma leitura de Vidas secas e La Muerte de Artemio Cruz - Oliveira, Jair Pereira de (2020)
The formation of modernity in the space-time Latin America caused a transformation in the conceptions of the subjectivities of individuals. When the European program arrived in that context, the Idea of the Self focused on the European, and the Other on the native. Due to constant struggles by emancipation and by building identities, this duality was being transformed. And the Self was taking the place of the Other. And this, the place of the Self. In this way, this research seeks to know if there is a founding process in symbolic images of the records formed since the contact between the local population and the European and its modern program and its consolidating; discuss the forms of subjectivation, subjectivity and subject which make it possible the recording of the images of the Latin America space-time; and, analyze the specific of one constitution of subjectivation on two literary expression grounded on the schizoanalytical view. Therefore, that research is developed through analysis of the expression of literary language, on how the constitution of altermnemonic subjectivation works (concept created here in the research and which consists of observing the coordinates of images that appear within the narratives, Vidas Secas and La Muerte de Artemio Cruz, in which subjectivities in contact with social machines lead to the production of desires that affect the construction of memory about the powers of life, in the experiments and the experiences that constitute the condition of being in the world, a condition permanently linked to the event). Therefore, we will make inroads on the concept of Latin America and the symbolic images that this concept evokes in the literature produced in this space-time. We will undertake psychoanalysis of history, a suggestion directed by Le Goff (1996), to understand the records of Real, Symbolic and Imaginary (RSI) (proposed by Lacan (1985; 1989; 2005; 2011)) to understand the formation of the Latin America concept, to resume aspects of the Real constituted in the symbolic images of the series of events that were articulated with this world, the result of the modern European program. When investigating the forms of the concept of Latin America, we will map the images of its faciality, applying Galeano (2004), Canclini (1989), Saguier (1972) among others. More analytically about the works being studied, we will cover the lines of literary expression with the tools provided by the schizoanalysis of Deleuze and Guattari (2011; 2012), Guattari and Solnik (1986), to understand which flows circulate in the joints between bodies and the social machines that drive a series of senses, perceptions, and affections. These are conductors of a memory that is overdetermined by the abstract machines that produce desire, in a movement that feeds back and delineates the faciality of altermnemonic subjectivation. The findings of this study consider that the altermnemonic subjectivation occur on the encounter within the symbol overdetermining forces of the modern European program.